Compassion for others, self-compassion, quality of life and mental well-being measures and their association with compassion fatigue and burnout in student midwives: A quantitative survey. (March 2016) - Beaumont, Elaine; Durkin, Mark; Hollins Martin, Caroline J.; Carson, Jerome
Abstract: Background: compassion fatigue and burnout can impact on the performance of midwives, with this quantitative paper exploring the relationship between self-compassion, burnout, compassion fatigue, self-judgement, self-kindness, compassion for others, professional quality of life and well-being of student midwives. Method: a quantitative survey measured relationships using questionnaires: (1) Professional Quality of Life Scale; (2) Self-Compassion Scale; (3) Short Warwick and Edinburgh Mental Well-being Scale; (4) Compassion For Others Scale. Participants: a purposive and convenience sample of student midwives ( n =103) studying at university participated in the study. Results: just over half of the sample reported above average scores for burnout. The results indicate that student midwives who report higher scores on the self-judgement sub-scale are less compassionate towards both themselves and others, have reduced well-being, and report greater burnout and compassion fatigue. Student midwives who report high on measures of self-compassion and well-being report less compassion fatigue and burnout. Conclusion: student midwives may find benefit from 'being kinder to self' in times of suffering, which could potentially help them to prepare for the emotional demands of practice and study. Implications: developing, creating and cultivating environments that foster compassionate care for self and others may play a significant role in helping midwives face the rigours of education and clinical practice during their degree programme. Highlights: Student midwives may benefit from being kinder to themselves in times of suffering. High self-compassion scores were linked with fewer symptoms of compassion fatigue. Over half of the sample reported above average scores for burnout. Cultivating self-compassion may help student midwives face the rigours of education. Self-judgement scores were linked with reduced well-being.